The image-concept of Russia in the British mass media texts (2017-2019) - Posternyak, Ksenia (Przegląd Wschodnioeuropejski, 2020)
The subject of this article are the linguistic means used to form the image-concept “Russia”. Corpus content analysis on the wide range material of the British print and electronic press for 2017-2019 is the base for constructing the nominative field with the core and near, far and final peripheries of image ”Russia”. The conceptual analysis revealed verbal means used for expansion of the concept volume and its component layers- metaphorical, nominative, evaluative and associative. These devices create the negative image-concept of state Russia in British public consciousness.